MDM2 Antagonists Counteract Drug-Induced DNA Damage - Vilgelm, Anna E. (EBioMedicine, 2017)
Antagonists of MDM2-p53 interaction are emerging anti-cancer drugs utilized in clinical trials for malignancies that rarely mutate p53, including melanoma. We discovered that MDM2-p53 antagonists protect DNA from drug-induced damage in melanoma cells and patient-derived xenografts. Among the tested DNA damaging drugs were various inhibitors of Aurora and Polo-like mitotic kinases, as well as traditional chemotherapy. Mitotic kinase inhibition causes mitotic slippage, DNA re-replication, and polyploidy. Here we show that re-replication of the polyploid genome generates replicative stress which leads to DNA damage. MDM2-p53 antagonists relieve replicative stress via the p53-dependent activation of p21 which inhibits DNA replication. Loss of p21 promoted drug-induced DNA damage in melanoma cells and enhanced anti-tumor activity of therapy combining MDM2 antagonist with mitotic kinase inhibitor in mice. In summary, MDM2 antagonists may reduce DNA damaging effects of anti-cancer drugs if they are administered together, while targeting p21 can improve the efficacy of such combinations.